2017
DOI: 10.1016/j.eurpsy.2017.02.179
|View full text |Cite
|
Sign up to set email alerts
|

Pressure From Superiors and Older Age Increase the Risk of Burnout Syndrome Among Psychiatric Trainees: A Nation-wide Survey in Turkey

Abstract: IntroductionPrevious studies reported high burnout rates and indicated significant factors associated with burnout syndrome among psychiatric trainees, such as hard working conditions, lack of supervision and not opting for psychiatry as a first career choice.ObjectivesA substantial amount of variance was reported in psychiatry training across countries. However, there is not sufficient national data regarding the rates and risk factors of burnout syndrome among psychiatric trainees in Turkey.AimsTo determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In that same vein, other studies reported that increasing age and greater occupational experience was positively associated with burnout. Among psychiatric trainees ( N = 167) in Turkey, logistic regression confirmed that older age ( p = 0.02) was associated with severe burnout [55]. Among nurses in Iran ( N = 200), greater age and work experience accounted for 30% of the variance in depersonalization [131].…”
Section: Resultsmentioning
confidence: 99%
“…In that same vein, other studies reported that increasing age and greater occupational experience was positively associated with burnout. Among psychiatric trainees ( N = 167) in Turkey, logistic regression confirmed that older age ( p = 0.02) was associated with severe burnout [55]. Among nurses in Iran ( N = 200), greater age and work experience accounted for 30% of the variance in depersonalization [131].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies reported that older age and more work experience were positively associated with burnout and psychological stress (46)(47)(48)(49)(50). Whereas other studies found that younger HCWs were more vulnerable to psychological disorders and older adults were less likely to develop burnout during pandemics (51,52).…”
Section: Discussionmentioning
confidence: 99%